The Relationship Between Knowledge, Attitudes, and Motivation in the Implementation of the Seven Rights of Medication Administration among Nursing Professional Students at Universitas Andalas - Ayu Andira; Zifriyanthi Minanda Putri; Yuanita Ananda (NERS Jurnal Keperawatan, 2026)
Medication administration errors continue to be a significant concern in patient safety, including among nursing professional students. This study aimed to analyze factors related to the implementation of the seven rights of medication administration among professional nursing students at Universitas Andalas. This quantitative study used a correlational design with a cross-sectional approach and involved 114 nursing professional students. Data were collected using questionnaires including ASPAM, and researcher-developed questionnaires were tested for validity using Pearson Correlation and reliability using Cronbach’s alpha, showing that all items are valid and reliable. Statistical analysis included univariate, bivariate, and multivariate tests, used Pearson Product-Moment correlation and multiple linear regression tests.  The findings indicated that students generally had high knowledge and motivation levels (mean= 13,44 and 47,73), along with positive attitudes (mean= 66,74), and good implementation practices (mean= 117,11). There were significant relationships between knowledge (p= 0,001), attitudes (p=0,000), and motivation (p=0,000) with implementation, and attitude identified as the most dominant factor. These findings highlight the need to strengthen patient safety attitudes through clinical learning strategies such as case studies and simulations, to improve students’ self-awareness, and to develop attitude-based interventional research to enhance the implementation of the seven rights of medication administration.